Water isotope variation in an ecohydrologic context at a seasonally dry tropical forest in northwest Mexico. (January 2022) - Castro-López, J.A.; Robles-Morua, A.; Méndez-Barroso, L.A.; Garatuza-Payan, J.; Rojas-Robles, O.A.; Yépez, E.A.
Abstract: We conducted an isotopic characterization of precipitation, streamflow, groundwater and bulk soil moisture (<60 cm depth) to assess ecohydrologic separation and its seasonal variation in a tropical dry forest in northwestern Mexico using four representative tree species. We present a data set that allows analyzing the connection of vegetation to soil or movable water in a highly seasonal ecosystem throughout one year (2015) but relies on baseline data set of local precipitation. A local meteoric water line was created using 5 years (2012–2017) of isotopic data ( δ 2 H = 7.64*δ 18 O + 7.34, r 2 = 0.97 ) at the study site. Ecohydrologic separation was clear throughout the dry season but during the wet monsoon season the upland trees L. divaricatum, A. cochliacanta and L. watsonii showed the opposite pattern since the isotopic composition of xylem water was similar to the meteoric water and shallow soil, stream and ground water. The riparian tree T. huegelii resulted in an isolated dynamic showing a similar isotopic composition to stream water. Results of this work suggest that ecohydrologic separation is not a universal pattern because it does not occur in all vegetation types and it may vary seasonally. Highlights: Ecohydrologic separation in tropical dry forest mostly occur during the dry season. Use of mobile water for the vegetation is apparent over the Monsoon season. Tree Ecohydrologic separation varies across species but display a general trend. Ecohydrologic separation is seasonally-dependent in tropical dry forests.